Relatório de estágio curricular supervisionado em medicina veterinária – área de clínica e cirurgia de pequenos animais - Cardoso, Gabriela Severo (2018)
The present work describes the activities carried out and monitored by the Gabriela Severo Cardoso, during the Supervised Curricular Internship in Veterinary Medicine, in the Small Animal Clinic and Surgery area. O internship took place from July 23 to October 19, 2018, at the Hospital Veterinarian Levet, in the City of Curitiba - PR, with guidance from Professor Dr. Roberto Thiesen and under the supervision of Veterinarian Dr. Luiz Felipe Ximenes Cibin, totaling 592 hours. The activities were concentrated in the clinic and small animal surgery, with a total of 125 cases followed up at the clinic, 103 canines and 22 felines, and 38 procedures followed in the surgery sector (30 dogs and 8 cats). The Supervised Curricular Internship in Veterinary Medicine (ECMV) has great value in academic training enabling the practice of all knowledge gained over the course. The practical experience in the medical clinic and surgery of small animals provided great learning, contributing to training and professional growth.